Evolution of the West African Mangrove During the Late Quaternary: A Review - Lézine, Anne-Marie (Géographie physique et Quaternaire, 1997)
ABSTRACTThe review of pollen data on mangrove pollen deposition in modern and late Quaternary sediments of West Africa points to two distinct signals linked to the sedimentary environment concerned. Along the littoral and on the slope of the continental shelf, mangrove peat deposits recording more than 40% of Rhizophora percentages reflect the postglacial sea-level rise and give evidence for the associated paleogeographical modifications (e.g. during the Nouakchottian transgression). Deep oceanic records show that the mangrove was present along the West African coasts during the Late Glacial Maximum reflecting local conditions of fresh water input and sea surface temperatures not as low as previously suggested. Mangrove developed after 12 500 BP as far north as 21°N; its maximum extension was recorded ca. 9500 BP reflecting the enhanced monsoon circulation over West Africa.